Evaluation of 2015-2016 MOTAKK HBV DNA and HCV RNA External Quality Assessment National Program Results - AKSU, MEHMET BURAK; DİNÇ, UĞUR ALP (ANKARA MICROBIOLOGY SOC, 2018)
MOTAKK, as a national external quality control program has been launched to evaluate the molecular detection of viral infections including HBV DNA and HCV RNA in molecular microbiology diagnostic laboratories in Turkey. This program is prepared in compliance with ISO 17043:2010 (Conformity assessment general requirements for proficiency testing) standards, and aims to take the place of external quality control programs from abroad, contributing to standardization and accuracy of molecular diagnostic tests in our country. The aim of this study was to evaluate 2015 and 2016 results of the MOTAKK External Quality Control Program for HBV DNA and HCV RNA viral load. The calls were announced on the web page of MOTAKK (www.motakk.org). The quality control samples were sent to participating laboratories in 2015 and 2016. Main stocks were prepared from patients with chronic hepatitis B and C who had viral load detection with reference methods according to WHO reference materials for viral load studies to improve quality control sera. From these main stocks, samples with different viral loads were prepared from dilutions of plasma with HBV, HCV, HAV, HIV, Parvovirus B19 and CMV negative serologic markers. Quality control samples were sent to the participating laboratories along with the negative samples in the cold chain. The laboratories accomplished the related tests within 2-3 weeks and entered their results on the MOTAKK web page. These results were analysed according to ISO 13528 (Statistical methods for use in proficiency testing by interlaboratory comparison) and scoring reports were created by a software developed by MOTAKK and sent to participating labs. Each laboratory evaluated their own results in comparison with the other laboratory results, reassessed the tests via observing the distance from the mean result and the reference values. The number of laboratories participating in the HBV DNA and HCV RNA external quality control program was 70-73 in 2015-2016. Participants were able to comply with the program tools, registering, entering results and receiving the results reports problem. In HBV panel, 72.6-89.1% and 84.7-90.3% of the participant laboratories were in 1 standard deviation (SD) in 2015-2016, respectively. In HCV panel, 70.8-89.1% and 84.7-90.3% of the participant laboratories were in 1 SD in 2015-2016, respectively. A national external quality control program for HBV DNA and HCV RNA in Turkey has been prepared for the first time with this project and implemented successfully. All the data provided in the MOTAKK external quality control program final report, compensate all the data provided by the quality control program final reports from abroad; additionally, the report allows comparison of used technologies and commercial products.
Keywords: HBV DNA; HCV RNA; external quality control; viral load; REAL-TIME PCR; HEPATITIS-B; CLINICAL MICROBIOLOGY; PROFICIENCY; TESTS